A Assembleia de Deus e a política aracajuana: análise da eleição de 2012 - Teixeira, Augusto César Santiago (2014)
This paper examines the strategies used by electoral candidates linked to the Church Assembly of God, the Municipality of Aracaju, in the election of 2012. Interpretive effort that sought to understand how this evangelical denomination structured their election campaigns. Thus, analyzes the relationship between evangelical pastors and vote, while canvassers. Focuses attention on the members who are chosen for candidacy for alderman; strategies and voting within the Church; strategies and the work of the vote outside the Church. The choice of the Assembly of God Church is due to the fact that having a longer foray into the political arena in Aracaju, dating from the 1980s. And among the findings highlight the evangelical candidate as a reality in Aracaju, despite these meld a set of strategies with old electoral religious practices, such welfarism. One notes also the importance of the candidate being a pastor and use social media (radio, television and internet) in winning votes, or even holding meetings and home visits to get closer to the electorate. It is in this environment that the woman plays an important role in winning voters.